An Analysis of the Application of the Journalistic Code of Ethics in Online Reporting on Sexual Harassment Via the Detik.com Media Portal - Raihana Atqiya (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
The development of social media has led to the expansion and proliferation of information media, enabling rapid access to information. However, the speed of access and the abundance of media do not guarantee adherence to the Journalistic Code of Ethics, which every journalist is expected to uphold. According to SIMFONI-PPA 2024, sexual harassment cases in 2023 were the most prevalent in Indonesia, with 13,156 reported cases. Given the sensitive nature of these cases for victims and their communities, this study employs Klaus KrippendorffÔÇÖs content analysis method to analyze 244 news articles published on Detik.com from January to March 2024, focusing on the application of the 11 articles of the Journalistic Code of Ethics in each report. Keywords: Content Analysis, Detik.com, Journalistic Code of Ethics, Klaus Krippendorff, Sexual Harassment.